2021
DOI: 10.3897/bdj.9.e69374
|View full text |Cite
|
Sign up to set email alerts
|

Life beneath the ice: jellyfish and ctenophores from the Ross Sea, Antarctica, with an image-based training set for machine learning

Abstract: Southern Ocean ecosystems are currently experiencing increased environmental changes and anthropogenic pressures, urging scientists to report on their biodiversity and biogeography. Two major taxonomically diverse and trophically important gelatinous zooplankton groups that have, however, stayed largely understudied until now are the cnidarian jellyfish and ctenophores. This data scarcity is predominantly due to many of these fragile, soft-bodied organisms being easily fragmented and/or destroyed with traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 693 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Namely, B. bouilloni, which is a true deep-sea Arctic species, was found in the lowest temperature conditions and deeper depths. In contrast, S. bitentaculata, which is a cosmopolitan species (although it has been suggested it may be actually composed of multiple cryptic species; (Lindsay et al, 2017;Verhaegen et al, 2021), was found across a wider temperature and depths ranges.…”
Section: Current State Of the Knowledge On Gelatinous Zooplankton In ...mentioning
confidence: 90%
“…Namely, B. bouilloni, which is a true deep-sea Arctic species, was found in the lowest temperature conditions and deeper depths. In contrast, S. bitentaculata, which is a cosmopolitan species (although it has been suggested it may be actually composed of multiple cryptic species; (Lindsay et al, 2017;Verhaegen et al, 2021), was found across a wider temperature and depths ranges.…”
Section: Current State Of the Knowledge On Gelatinous Zooplankton In ...mentioning
confidence: 90%
“…The A4 area sub-system was different from the other areas showing a completely different arrangement of chemicals and biological variables (Bolinesi et al, 2020). Zooplankton is the most important factor in regulating food web dynamics and ecological interactions in the Ross Sea (Hopkins, 1987;Saino and Guglielmo, 2000;Ainley et al, 2010;Ainley et al, 2015;Minutoli et al, 2017;Smith et al, 2017;Kiko et al, 2020) with gelatinous zooplankton, comprising jellyfish, ctenophores and chordate tunicates (Pagès, 1997), showing a ubiquitous behavior (Richardson et al, 2009;Schaub et al, 2018;Verhaegen et al, 2021). Nonetheless, zooplankton abundance varies greatly over the continental shelf and its assemblages, beyond copepods, are mainly composed by fish larvae, euphausiids, hyperiid and gammarid amphipods, pteropods, chaetognaths, and ostracods (Guglielmo et al, 1990;Guglielmo et al, 1992;Hecq et al, 1992;Hunt et al, 2008;Stevens et al, 2015;Smith et al, 2017;Granata et al, 2022;Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…the deep sea; Glover et al, 2018;Hughes et al, 2021; or polar marine ecosystems; e.g. Brandt et al, 2007;Verhaegen et al, 2021;Ramirez-Llodra et al, 2022). Only small fractions of many deep-sea ecosystems have been explored by biologists (Ramirez-Llodra et al, 2011;Rogers, 2015); with the deep pelagic being a particular challenge (Webb et al, 2010) because of its size, remoteness and the fragile nature of the organisms that inhabit it making them difficult to sample (e.g.…”
Section: Expeditionsmentioning
confidence: 99%